Peningkatan Keterampilan Bagi Ibu Rumah Tangga Dalam Rangka Penghematan Pengeluaran Melalui Pembuatan Sabun Cair Sederhana - Haro, Andrian; AWS Waspodo, Agung; Wahyu Handaru, Agung (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The consumption pattern of housewives in several things has already changed. Recently, there are so many housewives are switching to use liquid soap for cleaning their kitchen utensils. This is due to the ease of use of product and the affordable price. Regarding to this community service activity which has aims to improve the skills and knowledge of housewives, especially in IKADANA groups at Srengseng, West Jakarta, through the production of simple liquid soap in order to make savings in household consumption expenditure. This activity is performed by using the survey and demonstration method. The result show almost all participants have understood the process of making simple liquid soap and so far they are interested to try further in their own home, where one of the benefits of making this liquid soap is to save household expenditure, especially the consumption of liquid soap. More addition, the housewives become open-minded and motivated to make their skills as a side business or home industry to improve their household economy.